Retardation of oxidation and material degradation in biodiesel: a review - Sazzad, B.S.; Fazal, M.A.; Haseeb, A.S. Md. Abdul; Masjuki, Haji Hassan (Royal Society of Chemistry, 2016)
In the automobile sector, biodiesel has received considerable attention as a promising diesel substitute because of its enhanced lubricity and reduced emissions. Biodiesel is composed of both saturated and unsaturated fatty acid methyl esters. The unsaturated components of biodiesel make it susceptible to corrosion for automotive components. The corrosiveness of biodiesel and its blend can be attributed to its oxygen moieties, auto-oxidation, high polarity, and hygroscopic nature. These properties may also cause tribological degradation. The present study reviews different aspects of corrosion and tribological degradation of automotive materials in biodiesel. This review will help in understanding the major characteristics and the possible degradation mechanisms of corrosion for both ferrous and nonferrous metals in biodiesel. This article extends an overview of tribological degradation of automotive materials. Remedial measures and related mechanism for both corrosion and tribological degradation have also been emphasized which made this study unique from other reviews.